POTENT ANTIBACTERIAL EFFECTS OF TERMINALIA SUPERBA ENGL. AND DIELS (COMBRETACEAE) BARK EXTRACTS - Kougnimon, Fifamè Espérance Elvire; MEDEHOUENOU, THIERRY COMLAN MARC; MIGAN, Marcos A.D.F.; Akpovi, D. Casimir; LOKO, Frédéric (My University, 2023)
Antibiotic misuse has caused widespread multi-resistance in Enterobacteriaceae. Our study investigates Terminalia superba (T. superba) extracts against Extended spectrum beta-lactamases (ESBL)-producing strains. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined using broth microdilution (Mueller-Hinton, 106 CFU/mL). The extract concentrations ranged from 0.078 to 80 mg/mL. We evaluated T. superba extract's β-lactamase inhibition of nitrocefin hydrolysis, estimated inhibition percentages, and IC50 values for each extract. The double-disk test confirmed the presence of ESBLs in the strains, as all of them exhibited hydrolytic activity. The results indicated that the T. superba extracts displayed dose-dependent inhibitory effects on betalactamase. Among them, the hydro-ethanolic extract displayed potent inhibitory activity against β-lactamases produced by ESBL-E. coli (IC50 = 0.065 mg/mL), ESBL-K. pneumoniae (IC50 = 0.076 mg/mL), and ESBL-P. mirabilis (IC50 = 0.082 mg/mL). However, following the removal of tannins, the hydro-ethanolic extract's anti-β-lactamase activity was reduced. Our findings highlight the remarkable in vitro activity of T. superba extracts against ESBL-producing Enterobacteriaceae, suggesting their potential clinical utility in addressing infections caused by these drug-resistant pathogens. The exploration of T. superba extracts as a possible source of effective anti-ESBL agents could contribute significantly to combating antibiotic resistance.
Keywords: Terminalia Superba; Extended-Spectrum; Beta-Lactamases; Β-Lactamase Inhibitors; Antibacterial Activity